1999
DOI: 10.3354/meps179145
|View full text |Cite
|
Sign up to set email alerts
|

Selective feeding behavior of larval naked gobies Gobiosoma bosc and blennies Chasmodes bosquianus and Hypsoblennius hentzi:preferences for bivalve veligers

Abstract: Naked gobies Gobiosoma bosc, striped blennies Chasmodes bosquianus, and feather blennies Hypsoblennius hentzi provide important intermediate links within the trophic structure of estuarine oyster reef communities. Predator-prey interactions between planktonic larvae of these fishes and larval eastern oysters Crassostrea r~irginica may influence recruitment success within oyster reef communities. These 3 species of oyster reef fish larvae were cultured from wild nests and used in multifactorial laboratory feedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Thus, in agreement with some previous results for the northern hemisphere (Molloy et al . ; Harding ), we conclude that differences in the composition of fish species are largely responsible for the lower importance of Limnoperna veligers in the diet of the fish larvae of the Salto Grande reservoir, as compared with lotic waterbodies of the Paraná and Uruguay rivers.…”
Section: Discussionmentioning
confidence: 72%
“…Thus, in agreement with some previous results for the northern hemisphere (Molloy et al . ; Harding ), we conclude that differences in the composition of fish species are largely responsible for the lower importance of Limnoperna veligers in the diet of the fish larvae of the Salto Grande reservoir, as compared with lotic waterbodies of the Paraná and Uruguay rivers.…”
Section: Discussionmentioning
confidence: 72%
“…Some larval fishes have been found to feed substantially on veligers of other species, which provided nutritional benefits. Specifically, Gobiosoma bosc (Lacepède) (Naked Goby) and Hypsoblennius hentz (Lesueur) (Feather Blenny) larvae preferentially selected veligers of Crassostrea virginica (Gmelin) (Eastern Oyster) or Mercenaria mercenaria (L.) (Northern Quahog) even if the veligers were only 12% of the available food items (Harding 1999). Engraulis mordax Girard (North Pacific Anchovy) larvae grew in the laboratory on a diet of rotifers, Gymnodinium, and veligers (Lasker et al 1970, Theilacker andMcMaster 1971) although they very rarely eat veligers in nature (Arthur 1976).…”
Section: Discussionmentioning
confidence: 99%
“…However, the per capita consumption rate of G. bosc larvae, at 0.014 prey per individual per minute, was the lowest among the predator types examined. Harding (1999) reported a peak consumption rate of 0.03 prey per individual per minute in experimental trials and stated that, at a density of ten gobies per square meter, G. bosc could consume 74% of the natural larval production for oysters on a reef. A conversion of our observed feeding rates to an estimate of difference in instantaneous mortality (d) suggests that predation mortality could be much higher for C. ariakensis larvae than for C. virginica larvae assuming that the preferences and feeding rates we observed persist through demersal larval stages of G. bosc.…”
Section: Discussionmentioning
confidence: 97%
“…The rates of oyster larval predation by invertebrate predators at natural densities have been observed to be low in marine systems (Johnson and Shanks 2003). Yet, studies of oyster larval predation in estuaries such as Chesapeake Bay have found the predation rates to be significant on oyster larvae under natural conditions (Harding 1999;Purcell et al 1991), suggesting that the predation rate on bivalve larvae may be dependent on local prey density and the predator types present. In our experiments, the feeding rates of all predators were negligible below a prey density of 0.1 ml −1 , but oyster larvae are commonly found at densities as high as 200 ml −1 in Chesapeake Bay, particularly around oyster reefs (Chesapeake Bay monitoring program; http://www.chesapeakebay.net/data_plankton.aspx).…”
Section: Discussionmentioning
confidence: 98%